Studies on fresh milt parameters and cryopreservation of spermatozoa of endangered, golden mahseer, tor putitora (hamilton) - Ravindragouda Patil; Wazir Singh Lakra; Shrinivas Jahageerdar; Gopal Krishna; Asim Kumar Pal (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Physico-chemical parameters of fresh milt and mitochondrial activity of fresh spermatozoa of the endangered golden mahseer, Tor putitora (Hamilton) were investigated. Cryopreservation and fertility evaluation of cryopreserved-thawed spermatozoa of T. putitora were carried out. The concentration of spermatozoa and the spermatocrit values of the fresh milt were estimated to be 3.96±0.12 x 107 spermatozoa/ml and 70.00±1.53% respectively. The motility percentage of spermatozoa in the fresh milt was estimated to be 94.84±0.43. The elemental composition analysis revealed that the concentration of K+ was higher i.e., 14.13±0.32 mg/l when compared to that of Na+, Ca+, Mg+ and Zn+. The concentration of total reducing sugars and total proteins were estimated to be 51.79±0.47mg/100 ml and 40.57±0.75 mg/100ml respectively. The absorbance value of the fresh spermatozoa in Sperm Mitochnodrial Activity Index (SMAI) assessment by Nitro Blue Tetrazolium (NBT) assay was estimated to be 0.33±0.012. The optimum sperm: egg ratio was estimated to be 3.96 ±0.12 x 104+ no./egg. Hatching percentage of 45.97±1.72 was recorded for the cryopreserved-thawed spermatozoa while the fresh milt control recorded a hatching percentage of 73.10±0.82.